2022
DOI: 10.1021/acs.joc.2c00988
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Enabled Cascade Cyclization Reaction of Aromatic Aldehydes and Pyrazol-5-amines: Synthesis of Bis-pyrazolo[3,4-b:4′,3′-e]pyridines

Abstract: A facile method for the synthesis of bis-pyrazolo-[3,4-b:4′,3′-e]pyridines from easily available aromatic aldehydes and pyrazol-5-amines was developed via electrochemistry. The reaction proceeded smoothly under metal and external chemical oxidant-free conditions, giving a variety of bis-pyrazolo[3,4-b:4′,3′e]pyridines in moderate yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In 2014, 2021 and 2022, an effective synthesis of chromeno[2,3b]pyridines 3 and bis-pyrazolo[3,4-b:4′,3′-e]pyridines 6 containing pyridine ring has been realized by the electrochemical promoted cascade cyclization reactions of two components (Scheme 2). 9,10 The experimental results showed that the electrocatalytic reactions between salicylaldehyde 1 and three molecules of malononitrile 2 in the presence of NaBr afforded chromeno[2,3-b]pyridines 3 in 83-90% yields. 9 The electrochemically promoted cyclization reactions of aromatic aldehydes 4 with pyrazol-5-amines 5 furnished bispyrazolo[3,4-b:4′,3′-e]pyridines 6 in 11-77% yields.…”
Section: Synthesis Of Pyridines Quinolines Phenanthridines and Cinnol...mentioning
confidence: 99%
“…In 2014, 2021 and 2022, an effective synthesis of chromeno[2,3b]pyridines 3 and bis-pyrazolo[3,4-b:4′,3′-e]pyridines 6 containing pyridine ring has been realized by the electrochemical promoted cascade cyclization reactions of two components (Scheme 2). 9,10 The experimental results showed that the electrocatalytic reactions between salicylaldehyde 1 and three molecules of malononitrile 2 in the presence of NaBr afforded chromeno[2,3-b]pyridines 3 in 83-90% yields. 9 The electrochemically promoted cyclization reactions of aromatic aldehydes 4 with pyrazol-5-amines 5 furnished bispyrazolo[3,4-b:4′,3′-e]pyridines 6 in 11-77% yields.…”
Section: Synthesis Of Pyridines Quinolines Phenanthridines and Cinnol...mentioning
confidence: 99%
“…A cascade cancellation method involving paired electrolysis aims to achieve two objectives simultaneously: the direct synthesis of quinolines and the introduction of quinoline moieties into bioactive molecules. In the electro-reduction-induced cascade cancellation reaction, isatin (10) and dimethyl but-2-ynedioate (58) with a serine residue (60) were used as the starting materials. Under a constant current of 5 mA, graphite rod anode and platinum plate cathode with 20 mol% KI as an electrolyte in a simple undivided cell in CH 3 CN, the desired quinoline product (61) was obtained with moderate to excellent 40-99% yields.…”
Section: Imidazolesmentioning
confidence: 99%
“…Depending on the compound's composition, yields range from 40 to 68%. [60] Using the electrogenerated anion of ethanol as the base and sodium bromide as the supporting electrolyte, Hazeri et al described an efficient and convenient electrosynthesis process with a one-pot, three-component condensation reaction for the formation of 1,4-dihydropyrano[2,3-c]pyrazole derivatives (64) (Scheme 32). By employing an electrocatalytic tandem Knoevenagel-Michael reaction on malononitrile (5), aromatic aldehydes (1), and 3-methyl-1-phenyl-1H-pyrazol-5(4H)-one (62) in an undivided cell containing iron as a cathode and graphite as an anode, the reaction is carried out at room temperature with a constant current.…”
Section: Synthesis Of Six-membered N-containing Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, I − has been used as a versatile mediator in numerous annulation reactions for the preparation of 𝜋-conjugated heterocycles with more than two condensed aromatic rings. [100][101][102][103][104][105][106][107][108] For instance, the electrochemical oxidative cascade cyclization reactions of methyl azaarenes/ketones/aldehydes with pyrazol-5amines 34 was achieved to allow the formation of dipyrazolofused pyridines 35 [107,108] (Figure 9a), which have been assessed as electroluminescent materials for OLEDs owing to its strong fluorescence properties. [109][110][111] Traditional synthesis of dipyrazolo-fused pyridines usually required high temperature via a three-component reaction of pyrazol-5-amines and aromatic aldehydes.…”
Section: Electrochemical Syntheses Of Pahs With Halide Anions As the ...mentioning
confidence: 99%